Pengaruh Kompetensi, Motivasi dan Kinerja Guru serta Fasilitas Sekolah terhadap Keberhasilan Siswa dalam Menuntut Ilmu Melalui Proses Pembelajaran di Yayasan Pembangunan Ar-Ridho Kota Depok - Nurul Hamidah (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
ABSTRACT The purpose of this study is to discuss and analyze the Effect of Competence, Motivation and Teacher Performance and School Facilities on Student Success in Studying Knowledge Through the Learning Process at the Ar-Ridho Development Foundation, Depok City Methods and Types of data in this study, are quantitative data obtained through the results of a survey of students. This study uses primary data that is data obtained directly from respondents who filled out and developed the questionnaire through the Learning Process at the Ar-Ridho Development Foundation, Depok City. With a student population of approximately 1,508 students. The sample of this study was 125 students and alumni. Test the validity and reliability using SPSS 24.0. The statistical method used to test the hypothesis in this study uses the multivariate Structural Equation Modeling (SEM) technique with the software used is AMOS 18. The results of the research and testing of hypotheses that have a significant effect are as follows: 1. Teacher competence has no significant effect on the learning process. 2. Motivation does not significantly influence the learning process. 3. Teacher performance has a significant effect on the learning process. 4. Facilities have a significant effect on the learning process. 5. Competence does not significantly influence student success. 6. Motivation does not significantly influence student success. 7. Teacher performance does not significantly influence student success. 8. Facilities have a significant positive effect on student success. 9. The learning process has a significant effect on student success. Keywords: Teacher Competency (X1), Teacher Motivation (X2), Teacher Performance (X3), School Facilities (X4), Learning Process (Y1), Student Success (Y2)